2011
DOI: 10.2486/indhealth.ms1213
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Intratracheally Instilled Multiwall Carbon Nanotubes to Lung-Associated Lymph Nodes in Rats

Abstract: In order to assess the extrapulmonary effects of multiwall carbon nanotubes (MWCNT), deposition of MWCNT and histopathologic changes in lung-associated lymph nodes (LALN) were examined in MWCNT-administered rats. At the age of 13 wk, male F344 rats were intratracheally instilled with MWCNT at a dose of 0 (vehicle), 40 or 160 μg/rat. The rats were sacrificed on Day 1, 7, 28 or 91 after instillation and light microscopic examinations were performed on LALN tissues. MWCNT was translocated to right and left poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Translocation of MWCNT from the lung to the tracheobronchial lymph node has previously been demonstrated in rats (Aiso et al 2011). Increased paracortical cellularity has also been previously noted in the lymph nodes of rats inhaling MWCNT (Pauluhn 2010).…”
Section: Discussionmentioning
confidence: 87%
“…Translocation of MWCNT from the lung to the tracheobronchial lymph node has previously been demonstrated in rats (Aiso et al 2011). Increased paracortical cellularity has also been previously noted in the lymph nodes of rats inhaling MWCNT (Pauluhn 2010).…”
Section: Discussionmentioning
confidence: 87%
“…The authors noted that the deposition of the NMs was greater in the posterior mediastinal lymph node than in the parathymic lymph node. However, it should be noted that the presence of MWCNTs was evaluated by microscopic observations in haematoxylin and eosin-stained tissues (Aiso et al 2011). …”
Section: Intratracheal Instillationmentioning
confidence: 99%
“…Indeed, in vivo studies reported that MWCNT induced inflammation, granuloma formation, and persistent interstitial fibrosis (Porter et al, 2010; Takagi et al, 2008). Following intraperitonael (IP) administration, Aiso et al (2010; 2011) demonstrated that MWCNT were detected in the lung 60 days post-exposure. In vitro studies showed that exposure of lung and skin cells to MWCNT induced cytotoxic effects, oxidative stress, and genotoxic effects (Asakura et al, 2010; Patlolla et al, 2010; Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%